A Study on Systematic Risk and Expected Return of Event Driven Strategies in India - Mritunjay Mahato, A. K. Das Mohapatra (International Journal of Advanced Science and Technology, 2020)
This study examines the relationship that exists between systematic risk and expected return of Event Driven Hedge Strategies, namely, Special Situation Strategy, Activist Strategy, Credit Arbitrage Strategy, Merger Arbitrage Strategy, Distressed/Restructuring Strategy, and Multi-Strategy in comparison to S & P BSE 500. The data used in the study covers a period of 10 years from January 2008 to December 2017, collected from Hedge Fund Research Inc. and Eurekahedge. The data analyzed through Capital Assets Pricing Model (CAPM), ANOVA, Regression and Correlation reveals that there exists a positive correlation between Event Driven Strategies and S & P BSE 500. Further, the study reveals that out of the six Event driven strategies included in the study, it is for the Special Situation Strategy that the systematic risk and expected return have a strong relationship between. This implies that investors may prefer to adopt Special Situation Strategy over other strategies to maximize their profit.